Preparation method of nickel fiber

The method of pre-coating nickel wire with copper and using multiple drawing steps with annealing and electrolytic copper removal effectively addresses surface defects in nickel fibers, producing high-quality, cost-effective nickel fibers.

CN120311270APending Publication Date: 2025-07-15HUNAN HUITONG ADVANCED MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510392879.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The existing nickel fiber preparation methods are expensive and need to be carried out under high temperature vacuum environments. Surface defects such as scratches and cracks are prone to occur during mechanical drawing, which affects the quality and performance of the fiber.

Method used

Pre-nickel plating and copper plating are used to form a composite metal wire. Through continuous annealing and multiple passages of drawing, combined with electrolytic copper removal, nickel fibers with uniform diameter and smooth surface are prepared.

Benefits of technology

It realizes the preparation of nickel fibers with uniform diameter and smooth surface at low cost, avoids scratches and cracks during the drawing process, and improves the quality and performance of the fibers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nickel fiber preparation method, and relates to the technical field of metal fiber preparation, the nickel fiber preparation method comprises the following steps: selecting a nickel wire with the diameter of 0.2-1.0 mm, and sequentially carrying out deoiling activation solution soaking, nickel pre-plating, copper plating and drying to obtain a composite metal wire, the mass ratio of copper to nickel in the composite metal wire being (3-4): 20; multiple strands of composite metal wires are bundled and then loaded into a copper pipe to obtain a nickel-copper composite wire, and the nickel-copper composite wire is subjected to continuous annealing and multi-pass drawing to obtain a target diameter; and the nickel-copper composite wire is sequentially subjected to copper removal liquid soaking and electrolytic copper removal, and then the nickel fiber is obtained. According to the preparation method of the nickel fiber, the metal fiber with the single core diameter of 1-100 microns and the core number of 50-5000 strands can be prepared, the fiber diameter is uniform, the surface is smooth and not rough, and the manufacturing cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal fiber preparation, and particularly to a method for preparing nickel fibers. Background Art

[0002] Nickel fibers have wide applications in many fields such as electronics, aerospace, and chemical industry due to their good electrical conductivity, thermal conductivity, corrosion resistance, as well as relatively high strength and toughness. However, there are many deficiencies in traditional nickel fiber preparation methods. For example, the chemical vapor deposition method has high costs, and the reaction needs to be carried out in special environments such as high temperature and vacuum; the nickel fibers prepared by the melt spinning method have limitations in diameter uniformity and aspect ratio, and their performance stability is also poor.

[0003] The mechanical drawing method is an important method for preparing nickel fibers, but there are some problems in the existing mechanical drawing technology. For example, during the drawing process, the nickel fibers are prone to surface defects such as scratches and cracks, which seriously affect the quality and performance of the nickel fibers.

[0004] Therefore, it is of great practical significance to develop a mechanical drawing nickel fiber preparation method that can overcome the above problems. Summary of the Invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing nickel fibers, and the specific technical solution is as follows:

[0006] A method for preparing nickel fibers, comprising the following steps:

[0007] Step 1: Select nickel wires with a diameter of 0.2 - 1.0 mm, soak them in a degreasing activation solution, pre-plate nickel, plate copper, and then dry them to obtain composite metal wires, where the mass ratio of copper to nickel in the composite metal wires is (3 - 4):20;

[0008] Step 2: Bundle multiple strands of the composite metal wires and place them into a copper tube to obtain a nickel-copper composite wire, and then obtain the target diameter through continuous annealing and multiple passes of drawing;

[0009] Step 3: Soak the nickel-copper composite wire in a copper-removing solution and then electrolytically remove copper to obtain nickel fibers.

[0010] Preferably:

[0011] The degreasing activation solution is a mixed solution of a water-soluble emulsion with a concentration of 2% - 5% and sulfuric acid with a concentration of 1 - 2 mol / L, and the soaking time of the degreasing activation solution is 3 - 5 min;

[0012] The pre-nickel plating solution is prepared from the following components: nickel sulfate 200 - 250 g / L, hydrochloric acid 50 - 100 g / L, sodium sulfate 10 - 20 g / L, saccharin 0.2 - 0.5 g / L, and the solvent is water. When pre-nickel plating, the current density is 4 - 5 A / dm², the temperature of the plating solution is 30 - 50 °C, and the plating time is 5 - 10 min;

[0013] The copper plating solution is prepared from the following components: copper sulfate 150 - 200 g / L, sulfuric acid 70 - 100 g / L, and the solvent is water. When copper plating, the current density is 2 - 4 A / dm², the temperature of the plating solution is 20 - 40 °C, and the plating time is 30 - 50 min;

[0014] Preferably, the continuous annealing and multi-pass drawing specifically include:

[0015] Initial drawing: Select a drawing die with a hole diameter of (80 ± 2)% of the diameter of the nickel-copper composite wire, and the drawing speed is 0.5 m / s;

[0016] Subsequent drawing: The number of subsequent drawing passes is multiple. For multiple subsequent drawing passes, drawing dies with a hole diameter decreasing by 10% are sequentially selected, and the drawing speed is sequentially increased by 0.1 - 0.5 m / s, where the drawing speed of the last pass is 4 m / s;

[0017] Intermediate annealing: After the fifth drawing, place the nickel-copper composite wire in a heating furnace, heat it to 700 °C at a heating rate of 10 °C / min, and hold for 3 hours;

[0018] Post-treatment: After the last drawing, clean and dry the nickel-copper composite wire.

[0019] Preferably:

[0020] The copper removal solution is prepared from the following components: nitric acid 30 - 50 g / L, sulfuric acid 100 - 150 g / L, methylbenzotriazole 10 - 15 g / L, and the solvent is water. The soaking time in the copper removal solution is 40 - 50 min;

[0021] The electrolyte for electrolytic copper removal is prepared from the following components: ammonium citrate 100 - 150 g / L, sodium nitrate 150 - 200 g / L; sodium nitrite 50 - 70 g / L, and the solvent is water. When electrolytically removing copper, the temperature of the electrolyte is 30 - 40 °C, and the electrolytic voltage is 4 - 6 V.

[0022] Preferably, the soaking in the copper removal solution is used to remove 80% - 90% of the copper on the nickel-copper composite wire, and the electrolytic copper removal is used to remove the residual copper on the nickel-copper composite wire;

[0023] Preferably, the water-soluble emulsion is made of the following components: by weight percentage, fatty alcohol polyoxyethylene ether 1.5% - 3.5%, ethanol 0.4% - 1.2%, polyvinyl alcohol 0.08% - 0.25%, sodium benzoate 0.02% - 0.05%, and the balance is water.

[0024] Preferably, the degreasing activation liquid is made of the following components: by mass percentage, amino-functionalized nano-silicate dispersion 1% - 3%, perfluoropolyoxyethylene ether 0.5% - 1.5%, phosphoric acid 4.9% - 14.7%, sulfuric acid 4.9% - 9.8%, PEG-modified HEDP 0.1% - 0.5%, and the balance is water.

[0025] Preferably, the preparation of the amino-functionalized nano-silicate dispersion includes the following steps:

[0026] Add nano-silicate into deionized water and ultrasonically disperse for 30 min to form a nano-silicate suspension.

[0027] Adjust the pH of the suspension to 4 - 5 with 0.1 mol / L dilute hydrochloric acid or acetic acid and stir evenly.

[0028] Slowly drop the APTE step into the suspension while keeping stirring.

[0029] Place the mixture in a 60 °C water bath and stir for reaction for 4 - 6 h.

[0030] After the reaction ends, separate the solid product by a centrifuge and wash it 3 times each with ethanol and deionized water to remove the unreacted APTE step and by-products.

[0031] Disperse the washed solid in deionized water, adjust the concentration to 10% - 20%, and ultrasonically disperse for 15 min to obtain the amino-functionalized nano-silicate dispersion.

[0032] Preferably, the preparation of the perfluoropolyoxyethylene ether includes the following steps:

[0033] Add perfluorooctanol into absolute ethanol and stir to dissolve.

[0034] Add NaOH accounting for 1% of the mass of perfluorooctanol and stir evenly.

[0035] Under nitrogen protection, heat the reaction kettle to 70 - 80 °C, slowly introduce ethylene oxide gas with a molar ratio 5 - 10 times that of perfluorooctanol, and control the pressure at 0.2 - 0.5 MPa.

[0036] Keep at 70 - 80 °C and stir for reaction for 6 - 8 h until ethylene oxide is completely consumed.

[0037] After the reaction is completed, cool to room temperature, neutralize with dilute hydrochloric acid to a pH of 6 - 7, add deionized water, let it stand for liquid separation, and take the organic phase;

[0038] Remove ethanol and water with a rotary evaporator to obtain a viscous perfluoropolyoxyethylene ether product.

[0039] Preferably, the preparation of the PEG - modified HEDP includes the following steps:

[0040] Add the PEG after drying to remove moisture, 80% - concentrated HEDP, and 1% (by total mass) of p - T to a three - necked flask, and add toluene as a dehydrating agent;

[0041] Under a nitrogen atmosphere, heat to 110 - 120 °C and stir - reflux for 6 - 8 h;

[0042] After the reaction is completed, cool to room temperature, add deionized water to dissolve, let it stand for liquid separation, and take the aqueous phase;

[0043] Remove the residual toluene and water with a rotary evaporator to obtain PEG - modified HEDP.

[0044] The preparation method of the nickel fiber provided by the present invention has the following beneficial effects:

[0045] 1. Metal fibers with a single - core diameter of 1 - 100 μm and 50 - 5000 strands of cores can be prepared. The fiber diameter is uniform, the surface is smooth and not rough, and the production cost is low.

[0046] 2. Pre - plate nickel on the surface of the nickel wire and then plate copper to form a composite metal wire. The copper layer acts as a soft coating material and serves as a lubricating medium during the drawing process, reducing the direct friction between the nickel fiber and the die, thereby avoiding the generation of scratches and cracks.

[0047] 3. Bundle multiple strands of composite wires and load them into a copper tube to further utilize the ductility of copper to buffer the drawing stress. The copper - tube wrapping can prevent mutual scratching between multiple strands of fibers, and at the same time evenly disperse the drawing force and reduce local stress concentration.

[0048] 4. Continuous annealing eliminates work hardening, restores the plasticity of the material, and makes subsequent drawing easier. Reduce the diameter step - by - step in multiple passes, control the single - pass deformation amount, and avoid lattice distortion and surface cracking caused by large strains.

[0049] 5. Finally, use electrolysis to remove the copper layer, avoiding secondary damage that may be caused by mechanical peeling and ensuring the surface finish of the nickel fiber. Detailed implementation mode

[0050] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be described in detail below. The description of this part is only exemplary and explanatory, and should not have any restrictive effect on the protection scope of the present invention.

[0051] This embodiment provides a method for preparing nickel fibers, which includes the following steps:

[0052] Step 1: Select nickel wires with a diameter of 0.2 - 1.0 mm. After soaking in a degreasing activation solution, pre-plating nickel, plating copper, and drying in sequence, a composite metal wire is obtained. The mass ratio of copper to nickel in the composite metal wire is (3 - 4):20.

[0053] Step 2: Bundle multiple strands of the composite metal wire and load them into a copper tube to obtain a nickel-copper composite wire. After continuous annealing and multi-pass drawing, the target diameter is obtained.

[0054] Step 3: Soak the nickel-copper composite wire in a copper-removing solution and then electro-remove copper to obtain nickel fibers.

[0055] The method for preparing nickel fibers provided by this embodiment has the following beneficial effects:

[0056] 1. Metal fibers with a single-core diameter of 1 - 100 μm and a core number of 50 - 5000 strands can be obtained. The fiber diameter is uniform, the surface is smooth and not rough, and the manufacturing cost is low.

[0057] 2. Nickel is pre-plated on the surface of the nickel wire and then copper is plated to form a composite metal wire. The copper layer acts as a soft coating material and serves as a lubricating medium during the drawing process, reducing the direct friction between the nickel fibers and the die, thereby avoiding the generation of scratches and cracks.

[0058] 3. Bundle multiple strands of the composite wire and load them into a copper tube to further utilize the ductility of copper to buffer the drawing stress. The copper tube wrapping can prevent mutual scratching between multiple strands of fibers, and at the same time evenly disperse the drawing force, reducing local stress concentration.

[0059] 4. Continuous annealing eliminates work hardening and restores the plasticity of the material, making subsequent drawing easier. The diameter is gradually reduced in multiple passes, and the single-pass deformation amount is controlled to avoid lattice distortion and surface cracking caused by large strains.

[0060] 5. Finally, the copper layer is removed by electrolysis, avoiding secondary damage that may be caused by mechanical peeling and ensuring the surface finish of the nickel fibers.

[0061] Furthermore:

[0062] The degreasing activation solution is a mixed solution of a water-soluble emulsion with a concentration of 2% - 5% and sulfuric acid with a concentration of 1 - 2 mol / L. The soaking time in the degreasing activation solution is 3 - 5 min.

[0063] The pre - nickel - plating electroplating solution is made up of the following components: nickel sulfate 200 - 250 g / L, hydrochloric acid 50 - 100 g / L, sodium sulfate 10 - 20 g / L, saccharin 0.2 - 0.5 g / L, and the solvent is water. When pre - nickel - plating, the current density is 4 - 5 A / dm², the temperature of the electroplating solution is 30 - 50 °C, and the electroplating time is 5 - 10 min.

[0064] The copper - plating electroplating solution is made up of the following components: copper sulfate 150 - 200 g / L, sulfuric acid 70 - 100 g / L, and the solvent is water. When copper - plating, the current density is 2 - 4 A / dm², the temperature of the electroplating solution is 20 - 40 °C, and the electroplating time is 30 - 50 min.

[0065] Further, the continuous annealing and multi - pass drawing specifically include:

[0066] Initial drawing: Select a drawing die with a pore diameter of (80 ± 2)% of the diameter of the nickel - copper composite wire, and the drawing speed is 0.5 m / s.

[0067] Subsequent drawing: The number of subsequent drawing passes is multiple. For multiple subsequent drawing passes, drawing dies with pore diameters decreasing by 10% are selected in sequence, and the drawing speed is increased by 0.1 - 0.5 m / s in sequence, where the drawing speed of the last pass is 4 m / s.

[0068] Intermediate annealing: After the fifth drawing, place the nickel - copper composite wire in a heating furnace, heat it to 700 °C at a heating rate of 10 °C / min, and keep it at this temperature for 3 hours.

[0069] Post - treatment: After the last drawing, clean and dry the nickel - copper composite wire.

[0070] Further:

[0071] The copper - removing solution is made up of the following components: nitric acid 30 - 50 g / L, sulfuric acid 100 - 150 g / L, methylbenzotriazole 10 - 15 g / L, and the solvent is water. The soaking time in the copper - removing solution is 40 - 50 min.

[0072] The electrolyte for electrolytic copper - removal is made up of the following components: ammonium citrate 100 - 150 g / L, sodium nitrate 150 - 200 g / L, sodium nitrite 50 - 70 g / L, and the solvent is water. When electrolytically removing copper, the temperature of the electrolyte is 30 - 40 °C, and the electrolytic voltage is 4 - 6 V.

[0073] Further, soaking in the copper - removing solution is used to remove 80% - 90% of the copper on the nickel - copper composite wire, and electrolytic copper - removal is used to remove the residual copper on the nickel - copper composite wire.

[0074] Further, the water-soluble emulsion is made from the following components: by weight percentage, fatty alcohol polyoxyethylene ether 1.5% - 3.5%, ethanol 0.4% - 1.2%, polyvinyl alcohol 0.08% - 0.25%, sodium benzoate 0.02% - 0.05%, and the balance is water.

[0075] Further, the degreasing activation liquid is made from the following components: by mass percentage, amino-functionalized nano-silicate dispersion 1% - 3%, perfluoropolyoxyethylene ether 0.5% - 1.5%, phosphoric acid 4.9% - 14.7%, sulfuric acid 4.9% - 9.8%, PEG-modified HEDP 0.1% - 0.5%, and the balance is water.

[0076] Further, the preparation of the amino-functionalized nano-silicate dispersion includes the following steps:

[0077] Add nano-silicate into deionized water and ultrasonically disperse for 30 min to form a nano-silicate suspension.

[0078] Adjust the pH of the suspension to 4 - 5 with 0.1 mol / L dilute hydrochloric acid or acetic acid and stir evenly.

[0079] Slowly drop the APTE step into the suspension while keeping stirring.

[0080] Place the mixture in a 60 °C water bath and stir for reaction for 4 - 6 h.

[0081] After the reaction ends, separate the solid product with a centrifuge and wash it 3 times each with ethanol and deionized water to remove the unreacted APTE step and by-products.

[0082] Disperse the washed solid in deionized water, adjust the concentration to 10% - 20%, and ultrasonically disperse for 15 min to obtain the amino-functionalized nano-silicate dispersion.

[0083] The modification principle is as follows: Amino functional groups can form a weak coordination interaction with the nickel surface, improving the adsorption ability of silicate to fine particles and oils and further enhancing the cleaning effect; the functionalized nanoparticles can form a more uniform transition layer on the nickel surface, enhancing the bonding force of the pre-nickel plating layer and reducing peeling or cracks during drawing.

[0084] Further, the preparation of the perfluoropolyoxyethylene ether includes the following steps:

[0085] Add perfluorooctanol into absolute ethanol and stir to dissolve.

[0086] Add NaOH accounting for 1% of the mass of perfluorooctanol and stir evenly.

[0087] Under nitrogen protection, the reaction kettle was heated to 70 - 80 °C, and ethylene oxide gas with a molar ratio 5 - 10 times that of perfluorooctanol was slowly introduced, controlling the pressure at 0.2 - 0.5 MPa.

[0088] Maintain at 70 - 80 °C, stir and react for 6 - 8 h until the ethylene oxide is completely consumed.

[0089] After the reaction ended, it was cooled to room temperature, neutralized with dilute hydrochloric acid to pH 6 - 7, deionized water was added, allowed to stand for layering, and the organic phase was taken.

[0090] Ethanol and water were removed using a rotary evaporator to obtain a viscous perfluoropolyoxyethylene ether product.

[0091] The modification principle is as follows: Fluorosurfactants have extremely low surface tension and can more efficiently emulsify stubborn oils and organic pollutants; the fluorinated chains form a hydrophobic layer on the nickel surface, reducing the oxidation risk when exposed to air after degreasing activation, thereby reducing the surface stress concentration during drawing.

[0092] Furthermore, the preparation of PEG - modified HEDP includes the following steps:

[0093] The dried - to - remove - moisture PEG, 80% - concentrated HEDP, and 1% of the total mass of p - T were added to a three - necked flask in step A, and toluene was added as a dehydrating agent.

[0094] Under a nitrogen atmosphere, it was heated to 110 - 120 °C and stirred and refluxed for 6 - 8 h.

[0095] After the reaction ended, it was cooled to room temperature, deionized water was added for dissolution, allowed to stand for layering, and the aqueous phase was taken.

[0096] Residual toluene and water were removed using a rotary evaporator to obtain PEG - modified HEDP.

[0097] The modification principle is as follows: The block copolymer can form a denser organic film on the nickel surface, having both corrosion - inhibition and lubrication effects, reducing the friction damage during drawing; the phosphonic acid group retains the corrosion - inhibition and chelating functions, and the PEG chain improves the water solubility and stability of the formulation.

[0098] Specific examples are provided below. The provided examples can enable those skilled in the art to understand the present invention more comprehensively, but do not limit the present invention in any way.

[0099] Example 1

[0100] 1. Raw material preparation and pretreatment:

[0101] Nickel wires with a diameter of 0.5 mm were selected and cut into 5 - m wire segments.

[0102] Preparing degreasing and activating solution: Take a water-soluble emulsion (components: fatty alcohol polyoxyethylene ether 2.5 wt%, ethanol 0.8 wt%, polyvinyl alcohol 0.15 wt%, sodium benzoate 0.03 wt%, the balance is water), add it to water at 2.5 wt%, then add 1.5 mol / L sulfuric acid, mix evenly, and the total liquid volume is 2 L. Immerse the nickel wire in the degreasing and activating solution for 4 min at a temperature of 25 °C, take it out and rinse with distilled water.

[0103] Pre-plating nickel: Prepare an electroplating solution (nickel sulfate 220 g / L, hydrochloric acid 80 g / L, sodium sulfate 15 g / L, o-sulfobenzimide 0.3 g / L, solvent water), and the total liquid volume is 3 L. Place the nickel wire in the electroplating bath, with a current density of 4.5 A / dm 2 , electroplating bath temperature 40 °C, electroplating time 8 min, take it out after completion and wash with distilled water.

[0104] Copper plating: Prepare an electroplating solution (copper sulfate 180 g / L, sulfuric acid 85 g / L, solvent water), and the total liquid volume is 3 L. Place the nickel wire after pre-plating nickel in the electroplating bath, with a current density of 3 A / dm 2 , electroplating bath temperature 30 °C, electroplating time 40 min, dry it after completion (oven temperature 80 °C, time 20 min) to obtain a composite metal wire.

[0105] 2. Drawing to prepare nickel-copper composite wire:

[0106] Bundle 50 strands of the composite metal wire and place it in a copper tube with an outer diameter of 2.0 mm and an inner diameter of 1.6 mm to obtain a nickel-copper composite wire.

[0107] Multi-pass drawing, and the drawing parameters are shown in the following table:

[0108] Drawing times Die aperture (mm) Drawing speed (m / s) Remarks 1 1.28 0.5 Initial drawing 2 1.15 0.6 3 1.04 0.7 4 0.94 0.8 5 0.85 0.9 Continue after intermediate annealing 6 0.76 1.2 7 0.68 1.5 8 0.61 2.0 9 0.55 4.0 Final drawing

[0109] The intermediate annealing step is: Place the nickel-copper composite wire in a heating furnace, heat it to 700 °C at a rate of 10 °C / min, hold for 3 hours, and cool naturally.

[0110] 3. Copper removal treatment

[0111] Prepare a copper removal solution (nitric acid 40 g / L, sulfuric acid 120 g / L, methylbenzotriazole 12 g / L, solvent water), and the total liquid volume is 2 L. Immerse the nickel-copper composite wire in the copper removal solution for 45 min at a temperature of 25 °C, take it out and rinse with distilled water.

[0112] Electrolytic copper removal: Prepare an electrolytic solution (ammonium citrate 120 g / L, sodium nitrate 180 g / L, sodium nitrite 60 g / L, solvent is water), and the total liquid volume is 2 L. Place the composite wire in the electrolytic bath, with an electrolytic bath temperature of 35 °C, electrolytic voltage of 5 V, and electrolytic time of 20 min to remove the residual copper and obtain nickel fibers.

[0113] Cleaning and drying: Clean the nickel fibers with distilled water and dry them (80 °C, 20 min).

[0114] 4. Surface observation and diameter measurement:

[0115] Surface observation: Observe the surface of the nickel fibers using an optical microscope (magnification 1000 times) to check for defects such as scratches and cracks. Randomly select 5 sample areas for observation and record the number of surface defects.

[0116] Diameter measurement: Measure the diameter of the nickel fibers using a high-precision digital micrometer. Uniformly select 10 points on each sample in the length direction for measurement and calculate the average diameter. Repeat the preparation of 3 batches of nickel fibers and record the data as the average value.

[0117] The test data is shown in the following table:

[0118] Sample number Average diameter (μm) Number of surface defects (per field of view) 1 50.12 0 2 50.08 0 3 50.15 1 Average value 50.11 0.33

[0119] Data analysis: The average diameter of the nickel fibers is approximately 50.11 μm, and there are very few surface defects, indicating that this method effectively solves the problems of surface scratches and cracks in mechanical drawing.

[0120] Example 2

[0121] 1. Raw material preparation and pretreatment:

[0122] Select nickel wires with a diameter of 0.5 mm and cut them into 5 m wire segments.

[0123] Prepare the degreasing and activating solution: Take a water-soluble emulsion (components: fatty alcohol polyoxyethylene ether 3.0 wt%, ethanol 1.0 wt%, polyvinyl alcohol 0.20 wt%, sodium benzoate 0.04 wt%, the balance is water) and add it to water at 3.0 wt%, then add 1.8 mol / L sulfuric acid and mix evenly. The total liquid volume is 2 L. Immerse the nickel wires in the degreasing and activating solution for 5 min at a temperature of 25 °C, take them out and rinse with distilled water.

[0124] Pre-plating nickel: Prepare the electroplating solution (nickel sulfate 230 g / L, hydrochloric acid 90 g / L, sodium sulfate 18 g / L, saccharin 0.4 g / L, solvent water), and the total liquid volume is 3 L. Place the nickel wires in the electroplating bath, with a current density of 4.8 A / dm 2 , the temperature of the electroplating solution is 45 °C, and the electroplating time is 10 min. After completion, take them out and rinse with distilled water.

[0125] Copper plating: Prepare the electroplating solution (copper sulfate 190 g / L, sulfuric acid 90 g / L, solvent water), and the total liquid volume is 3 L. Place the nickel wires after pre-plating nickel in the electroplating bath, with a current density of 3.5 A / dm 2, the temperature of the electroplating solution is 35°C, the electroplating time is 45 min, and after completion, it is dried (oven temperature 80°C, time 20 min) to obtain the composite metal wire.

[0126] 2. Drawing to prepare the nickel-copper composite wire:

[0127] Bundle 200 strands of the composite metal wire and load them into a copper tube with an outer diameter of 4.0 mm and an inner diameter of 3.2 mm to obtain the nickel-copper composite wire.

[0128] Multi-pass drawing, and the drawing parameters are shown in the following table:

[0129] Drawing times Die aperture (mm) Drawing speed (m / s) Remarks 1 2.56 0.5 Initial drawing 2 2.30 0.6 3 2.07 0.7 4 1.86 0.8 5 1.67 0.9 Continue after intermediate annealing 6 1.50 1.2 7 1.35 1.5 8 1.22 2.0 9 1.10 4.0 Final drawing

[0130] The intermediate annealing step is as follows: Place the nickel-copper composite wire in a heating furnace, heat it to 700°C at a rate of 10°C / min, hold for 3 hours, and cool naturally.

[0131] 3. Copper removal treatment

[0132] Prepare the copper removal solution (40 g / L of nitric acid, 120 g / L of sulfuric acid, 12 g / L of methylbenzotriazole, and solvent water), with a total liquid volume of 2 L. Immerse the nickel-copper composite wire in the copper removal solution for 50 min at a temperature of 25°C, and after taking it out, rinse it with distilled water.

[0133] Electrolytic copper removal: Prepare the electrolyte (120 g / L of ammonium citrate, 180 g / L of sodium nitrate, 60 g / L of sodium nitrite, and the solvent is water), with a total liquid volume of 2 L. Place the composite wire in the electrolytic cell, with the electrolyte temperature of 35°C, the electrolytic voltage of 5 V, and the electrolytic time of 25 min to remove the residual copper and obtain nickel fibers.

[0134] Washing and drying: Wash the nickel fibers with distilled water and dry them (80°C, 20 min).

[0135] 4. Surface observation and diameter measurement:

[0136] Surface observation: Observe the surface of the nickel fibers using an optical microscope (magnification 1000 times) to check for defects such as scratches and cracks. Randomly select 5 sample areas for observation and record the number of surface defects.

[0137] Diameter measurement: Measure the diameter of the nickel fibers using a high-precision digital micrometer. Uniformly select 10 points on each sample in the length direction for measurement and calculate the average diameter. Repeat the preparation of 3 batches of nickel fibers and record the data by taking the average value.

[0138] The test data are shown in the following table:

[0139] Sample number Average diameter (μm) Number of surface defects (per field of view) 1 50.20 0 2 50.17 1 3 50.23 0 Average value 50.20 0.33

[0140] Data analysis: In Example 2, the number of strands increased to 200, and the dosages of some components were slightly adjusted. The average diameter of the nickel fibers was about 50.20 μm, and the surface quality was good, which was consistent with Example 1, indicating that the method has strong adaptability to different numbers of strands.

[0141] Example 3

[0142] 1. Raw material preparation and pretreatment:

[0143] Select nickel wires with a diameter of 0.5 mm and cut them into 5 m wire segments.

[0144] Preparation of degreasing and activating solution:

[0145] Preparation of amino-functionalized nano-silicate dispersion: Add 10 g of nano-silicate to 90 g of deionized water and ultrasonically disperse for 30 min; adjust the pH to 4.5 with 0.1 mol / L dilute hydrochloric acid and stir evenly; slowly add 5 g of APTES (3-aminopropyltriethoxysilane) and react with stirring in a water bath at 60 °C for 5 h; centrifuge to separate the solid, wash it 3 times with ethanol and deionized water respectively, disperse it in deionized water, adjust the concentration to 15%, and ultrasonically disperse for 15 min to obtain the amino-functionalized nano-silicate dispersion.

[0146] Preparation of perfluoropolyoxyethylene ether: Dissolve 50 g of perfluorooctanol in 100 mL of absolute ethanol, add 0.5 g of NaOH and stir evenly; under nitrogen protection, heat up to 75 °C, introduce 176 g of ethylene oxide, control the pressure at 0.3 MPa, and react with stirring for 7 h; after cooling, neutralize it to pH 6.5 with dilute hydrochloric acid, separate the organic phase by layering, and rotary evaporate to remove ethanol and water to obtain perfluoropolyoxyethylene ether.

[0147] Preparation of PEG-modified HEDP: Add 20 g of PEG, 20 g of 80% HEDP, and 0.4 g of p-TSA to a three-necked flask, and add 50 mL of toluene; heat up to 115 °C under nitrogen and reflux for 7 h; after cooling, dissolve it with deionized water, separate the aqueous phase by layering, and rotary evaporate to remove toluene and water to obtain PEG-modified HEDP.

[0148] Prepare the degreasing and activating solution: 2 wt% of amino-functionalized nano-silicate dispersion, 1 wt% of perfluoropolyoxyethylene ether, 10 wt% of phosphoric acid, 7 wt% of sulfuric acid, 0.3 wt% of PEG-modified HEDP, and the balance is water, with a total liquid volume of 2 L. Immerse the nickel wires in the degreasing and activating solution for 4 min at 25 °C, take them out and rinse with distilled water.

[0149] Pre-plating nickel: Prepare the electroplating solution (nickel sulfate 220 g / L, hydrochloric acid 80 g / L, sodium sulfate 15 g / L, o-sulfobenzimide 0.3 g / L, solvent water), with a total liquid volume of 3 L. Place the nickel wires in the electroplating bath, and the current density is 4.5 A / dm 2, the temperature of the electroplating solution is 40°C, the electroplating time is 8 min. After completion, take it out and wash it with distilled water.

[0150] Copper plating: Prepare the electroplating solution (180 g / L of copper sulfate, 85 g / L of sulfuric acid, solvent water), and the total liquid volume is 3 L. Place the nickel wire after pre-nickel plating in the electroplating bath, and the current density is 3 A / dm 2 , the temperature of the electroplating solution is 30°C, the electroplating time is 40 min. After completion, dry it (oven temperature 80°C, time 20 min) to obtain the composite metal wire.

[0151] 2. Drawing to prepare nickel-copper composite wire:

[0152] Bundle 50 strands of the composite metal wire and put them into a copper tube with an outer diameter of 2.0 mm and an inner diameter of 1.6 mm to obtain the nickel-copper composite wire.

[0153] Multi-pass drawing, and the drawing parameters are shown in the following table:

[0154] Drawing times Die aperture (mm) Drawing speed (m / s) Remarks 1 1.28 0.5 Initial drawing 2 1.15 0.6 3 1.04 0.7 4 0.94 0.8 5 0.85 0.9 Continue after intermediate annealing 6 0.76 1.2 7 0.68 1.5 8 0.61 2.0 9 0.55 4.0 Final drawing

[0155] The intermediate annealing step is as follows: Place the nickel-copper composite wire in a heating furnace, heat it to 700°C at a rate of 10°C / min, hold for 3 hours, and cool naturally.

[0156] 3. Copper removal treatment

[0157] Prepare the copper removal solution (40 g / L of nitric acid, 120 g / L of sulfuric acid, 12 g / L of methylbenzotriazole, solvent water), and the total liquid volume is 2 L. Immerse the nickel-copper composite wire in the copper removal solution for 45 min at a temperature of 25°C. After taking it out, rinse it with distilled water.

[0158] Electrolytic copper removal: Prepare the electrolytic solution (120 g / L of ammonium citrate, 180 g / L of sodium nitrate, 60 g / L of sodium nitrite, solvent is water), and the total liquid volume is 2 L. Place the composite wire in the electrolytic bath, the temperature of the electrolytic solution is 35°C, the electrolytic voltage is 5 V, and the electrolytic time is 20 min to remove the residual copper and obtain nickel fibers.

[0159] Washing and drying: Wash the nickel fibers with distilled water and dry them (80°C, 20 min).

[0160] 4. Surface observation and diameter measurement:

[0161] Surface observation: Use an optical microscope (magnification 1000 times) to observe the surface of the nickel fibers and check for defects such as scratches and cracks. Randomly select 5 sample areas for observation and record the number of surface defects.

[0162] Diameter measurement: Use a high-precision digital micrometer to measure the diameter of nickel fibers. Select 10 points evenly in the length direction of each sample for measurement, and calculate the average diameter. Repeat the preparation of 3 batches of nickel fibers, and record the data by taking the average value.

[0163] The test data are shown in the following table:

[0164] Sample number Average diameter (μm) Number of surface defects (per field of view) 1 50.10 0 2 50.07 0 3 50.13 0 Average value 50.10 0

[0165] Data analysis: After using the new degreasing and activating solution, the average diameter of nickel fibers is 50.10 μm, and there are no defects on the surface, indicating that the new formula has a better surface treatment effect on nickel wires and the fiber quality is stable.

[0166] Example 4

[0167] 1. Raw material preparation and pretreatment:

[0168] Select nickel wires with a diameter of 0.5 mm and cut them into 5 m wire segments.

[0169] Preparation of degreasing and activating solution:

[0170] Preparation of amino-functionalized nanosilicate dispersion: Add 10 g of nanosilicate to 90 g of deionized water and ultrasonically disperse for 30 min; adjust the pH to 4.5 with 0.1 mol / L dilute hydrochloric acid and stir evenly; slowly add 5 g of APTES (3-aminopropyltriethoxysilane), stir and react in a water bath at 60 °C for 5 h; centrifuge to separate the solid, wash it 3 times with ethanol and deionized water respectively, disperse it in deionized water, adjust the concentration to 15%, and ultrasonically disperse for 15 min to obtain amino-functionalized nanosilicate dispersion.

[0171] Preparation of perfluoropolyoxyethylene ether: Dissolve 50 g of perfluorooctanol in 100 mL of absolute ethanol, add 0.5 g of NaOH and stir evenly; under nitrogen protection, heat up to 75 °C, introduce 176 g of ethylene oxide, control the pressure at 0.3 MPa, and stir and react for 7 h; after cooling, neutralize to pH 6.5 with dilute hydrochloric acid, separate the organic phase by layering, and rotary evaporate to remove ethanol and water to obtain perfluoropolyoxyethylene ether.

[0172] Preparation of PEG-modified HEDP: Add 20 g of PEG, 20 g of 80% HEDP, and 0.4 g of p-TSA to a three-necked flask, and add 50 mL of toluene; heat up to 115 °C under nitrogen and reflux for 7 h; after cooling, dissolve it with deionized water, separate the aqueous phase by layering, and rotary evaporate to remove toluene and water to obtain PEG-modified HEDP.

[0173] Configure degreasing and activating solution: 2 wt% of amino-functionalized nano-silicate dispersion, 1 wt% of perfluoropolyoxyethylene ether, 10 wt% of phosphoric acid, 7 wt% of sulfuric acid, 0.3 wt% of PEG-modified HEDP, and the balance is water, with a total liquid volume of 2 L. Soak for 5 min at 25 °C, then take out and wash.

[0174] Pre-plate nickel: Configure electroplating solution (230 g / L of nickel sulfate, 90 g / L of hydrochloric acid, 18 g / L of sodium sulfate, 0.4 g / L of saccharin, and the solvent is water), with a total liquid volume of 3 L. Current density is 4.8 A / dm 2 , at 45 °C for 10 min, then wash.

[0175] Plate copper: Configure electroplating solution (190 g / L of copper sulfate, 90 g / L of sulfuric acid, and the solvent is water), with a total liquid volume of 3 L. Current density is 3.5 A / dm 2 , at 35 °C for 45 min, then dry (at 80 °C for 20 min) to obtain composite metal wire.

[0176] 2. Draw to prepare nickel-copper composite wire:

[0177] Bundle 200 strands of composite metal wire and put them into a copper tube with an outer diameter of 4.0 mm and an inner diameter of 3.2 mm to obtain nickel-copper composite wire.

[0178] Multi-pass drawing, and the drawing parameters are shown in the following table:

[0179] Drawing times Die aperture (mm) Drawing speed (m / s) Remarks 1 2.56 0.5 Initial drawing 2 2.30 0.6 3 2.07 0.7 4 1.86 0.8 5 1.67 0.9 Continue after intermediate annealing 6 1.50 1.2 7 1.35 1.5 8 1.22 2.0 9 1.10 4.0 Final drawing

[0180] The intermediate annealing step is: Place the nickel-copper composite wire in a heating furnace, heat it to 700 °C at a rate of 10 °C / min, hold for 3 hours, and then cool naturally.

[0181] 3. Copper removal treatment

[0182] Configure copper removal solution (40 g / L of nitric acid, 120 g / L of sulfuric acid, 12 g / L of methylbenzotriazole, and the solvent is water), with a total liquid volume of 2 L. Soak for 50 min at 25 °C to remove 85% of copper, then wash.

[0183] Electrolytic copper removal: Electrolyte (120 g / L of ammonium citrate, 180 g / L of sodium nitrate, 60 g / L of sodium nitrite, and the solvent is water), with a total liquid volume of 2 L, at 35 °C, voltage of 5 V, electrolyze for 25 min to remove the remaining copper, obtain nickel fibers, and then wash and dry (at 80 °C for 20 min).

[0184] 4. Surface observation and diameter measurement:

[0185] Surface Observation: Observe the surface of nickel fibers using an optical microscope (magnification 1000x) to check for defects such as scratches and cracks. Randomly select 5 sample areas for observation and record the number of surface defects.

[0186] Diameter Measurement: Measure the diameter of nickel fibers using a high-precision digital micrometer. Uniformly select 10 points for measurement in the length direction of each sample and calculate the average diameter. Repeat the preparation of 3 batches of nickel fibers and record the average value of the data.

[0187] The test data is shown in the following table:

[0188] Sample number Average diameter (μm) Number of surface defects (per field of view) 1 50.18 0 2 50.15 0 3 50.21 0 Average value 50.18 0

[0189] Data Analysis: In Example 4, a new type of degreasing and activating solution was used under the condition of 200 strands. The average diameter of the nickel fibers was 50.18 μm, and the surface quality was excellent. Compared with Example 2, the new formula optimized the surface treatment effect and was suitable for multi-strand preparation.

[0190] Comparative Example 1

[0191] 1. Raw Material Preparation and Pretreatment:

[0192] Select nickel wires with a diameter of 0.5 mm and cut them into 5 m wire segments.

[0193] 2. Drawing to Prepare Nickel-Copper Composite Wire

[0194] Bundle 50 strands of nickel wires and load them into a copper tube with an outer diameter of 2.0 mm and an inner diameter of 1.6 mm to obtain a nickel-copper composite wire.

[0195] Multi-pass drawing, and the drawing parameters are shown in the following table:

[0196] Drawing times Die aperture (mm) Drawing speed (m / s) Remarks 1 1.28 0.5 Initial drawing 2 1.15 0.6 3 1.04 0.7 4 0.94 0.8 5 0.85 0.9 Continue after intermediate annealing 6 0.76 1.2 7 0.68 1.5 8 0.61 2.0 9 0.55 4.0 Final drawing

[0197] The intermediate annealing step is as follows: Place the nickel-copper composite wire in a heating furnace, heat it to 700 °C at a rate of 10 °C / min, hold for 3 hours, and then cool naturally.

[0198] 3. Copper Removal Treatment

[0199] Prepare a copper removal solution (40 g / L nitric acid, 120 g / L sulfuric acid, 12 g / L methylbenzotriazole, solvent is water), with a total liquid volume of 2 L, soak for 45 min at a temperature of 25 °C, remove the copper tube, and wash.

[0200] Electrolytic copper removal: The electrolytic solution (120 g / L ammonium citrate, 180 g / L sodium nitrate, 60 g / L sodium nitrite, solvent is water), with a total liquid volume of 2 L, at a temperature of 35 °C, a voltage of 5 V, electrolyze for 20 min to remove the residual copper, obtain nickel fibers, and wash and dry (80 °C, 20 min).

[0201] 4. Surface observation and diameter measurement:

[0202] Surface observation: Use an optical microscope (magnification 1000 times) to observe the surface of the nickel fiber to check for scratches, cracks and other defects. Randomly select 5 sample areas for observation and record the number of surface defects.

[0203] Diameter measurement: Use a high-precision digital micrometer to measure the diameter of the nickel fiber. For each sample, 10 points are evenly selected along the length direction to measure and the average diameter is calculated. Repeat the preparation of 3 batches of nickel fibers and take the average value to record the data.

[0204] The test data is shown in the following table:

[0205] Sample number Average diameter (μm) Number of surface defects (per field of view) 1 50.35 5 2 50.42 6 3 50.28 4 Average value 50.35 5.00

[0206] Data analysis: In comparative example 1, the nickel wires were not soaked in oil activation liquid, pre-nickel plated, or copper plated. The nickel wires were simply bundled into multiple strands and directly loaded into the copper tube, resulting in a large number of fiber surface defects.

[0207] Comparative Example 2

[0208] 1. Raw material preparation and pretreatment:

[0209] Select a nickel wire with a diameter of 0.5 mm and cut it into 5 m wire segments.

[0210] 2. Drawing and preparing nickel-copper composite wire:

[0211] 200 strands of composite metal wires were bundled and loaded into a copper tube with an outer diameter of 4.0 mm and an inner diameter of 3.2 mm to obtain a nickel-copper composite wire.

[0212] Multi-pass drawing, the drawing parameters are shown in the following table:

[0213] Drawing times Die aperture (mm) Drawing speed (m / s) Remarks 1 2.56 0.5 Initial drawing 2 2.30 0.6 3 2.07 0.7 4 1.86 0.8 5 1.67 0.9 Continue after intermediate annealing 6 1.50 1.2 7 1.35 1.5 8 1.22 2.0 9 1.10 4.0 Final drawing

[0214] The intermediate annealing step is: placing the nickel-copper composite wire in a heating furnace, heating it to 700°C at 10°C / min, keeping it at that temperature for 3 hours, and cooling it naturally.

[0215] 3. Copper removal

[0216] Prepare copper removal solution (40 g / L nitric acid, 120 g / L sulfuric acid, 12 g / L methylbenzotriazole, and water as solvent), with a total liquid volume of 2 L, soak for 50 minutes, at a temperature of 25°C, remove the copper tube, and clean it.

[0217] Electrolytic removal of copper: electrolyte (ammonium citrate 120g / L, sodium nitrate 180g / L, sodium nitrite 60g / L, solvent is water), total liquid volume 2L, temperature 35°C, voltage 5V, electrolysis for 25min, remove residual copper, obtain nickel fiber, wash and dry (80°C, 20min).

[0218] 4. Surface Observation and Diameter Measurement:

[0219] Surface Observation: Observe the surface of nickel fibers using an optical microscope (magnification: 1000 times) to check for defects such as scratches and cracks. Randomly select 5 sample areas for observation and record the number of surface defects.

[0220] Diameter Measurement: Measure the diameter of nickel fibers using a high-precision digital micrometer. Uniformly select 10 points for measurement in the length direction of each sample, and calculate the average diameter. Repeat the preparation of 3 batches of nickel fibers and record the average value of the data.

[0221] The test data is shown in the following table:

[0222] Sample number Average diameter (μm) Number of surface defects (per field of view) 1 50.45 7 2 50.38 6 3 50.52 6 Average value 50.45 6.33

[0223] Data Analysis: In Comparative Example 2, the number of strands increased to 200. Without soaking in the degreasing activation solution, without pre-plating nickel, and without plating copper, only the nickel wires were bundled into a multi-strand and directly inserted into the copper tube and then drawn. The number of surface defects was more than that in Comparative Example 1.

[0224] Combining Examples 1-4 and Comparative Examples 1-2, it can be seen that the pretreatment steps (soaking in the degreasing activation solution, pre-plating nickel, and plating copper) can improve the quality of the prepared nickel fibers, and the improved degreasing activation solution can further reduce the number of surface defects, thereby improving the quality and performance of nickel fibers.

[0225] Specific examples are used in this article to elaborate on the principles and implementation methods of the present invention. The descriptions of the above examples are only used to help understand the method and its core idea of the present invention. The above are only the preferred implementation methods of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the technical field, within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, makes equivalent substitutions or changes, and should be within the protection scope of the present invention.

Claims

1. A method for preparing nickel fibers, characterized in that, It includes the following steps: S1: Select a nickel wire with a diameter of 0.2 - 1.0 mm. After being soaked in a degreasing and activating solution, pre-plated with nickel, plated with copper, and dried in sequence, a composite metal wire is obtained. The mass ratio of copper to nickel in the composite metal wire is (3 - 4):20; S2: Bundle multiple strands of the composite metal wire and load them into a copper tube to obtain a nickel-copper composite wire. After continuous annealing and multi-pass drawing, the target diameter is obtained; S3: Soak the nickel-copper composite wire in a copper-removing solution and then perform electrolytic copper removal to obtain nickel fibers.

2. The preparation method according to claim 1, wherein: The degreasing and activating solution is a mixed solution of a water-soluble emulsion with a concentration of 2% - 5% and sulfuric acid with a concentration of 1 - 2 mol / L. The soaking time in the degreasing and activating solution is 3 - 5 min; The electroplating solution for pre-plating nickel is made of the following components: nickel sulfate 200 - 250 g / L, hydrochloric acid 50 - 100 g / L, sodium sulfate 10 - 20 g / L, o-sulfobenzimide 0.2 - 0.5 g / L, and the solvent is water. When pre-plating nickel, the current density is 4 - 5 A / dm², the temperature of the electroplating solution is 30 - 50 °C, and the electroplating time is 5 - 10 min; The electroplating solution for plating copper is made of the following components: copper sulfate 150 - 200 g / L, sulfuric acid 70 - 100 g / L, and the solvent is water. When plating copper, the current density is 2 - 4 A / dm², the temperature of the electroplating solution is 20 - 40 °C, and the electroplating time is 30 - 50 min.

3. The preparation method according to claim 1, characterized in that, The continuous annealing and multi-pass drawing specifically include: Initial drawing: Select a drawing die with a pore diameter of (80 ± 2)% of the diameter of the nickel-copper composite wire, and the drawing speed is 0.5 m / s; Subsequent drawing: The number of subsequent drawing times is multiple. For multiple subsequent drawings, drawing dies with pore diameters decreasing by 10% are selected in sequence, and the drawing speeds are increased by 0.1 - 0.5 m / s in sequence, where the drawing speed of the last drawing is 4 m / s; Intermediate annealing: After the fifth drawing, place the nickel-copper composite wire in a heating furnace, heat it to 700 °C at a heating rate of 10 °C / min, and keep it warm for 3 hours; Post-treatment: After the last drawing, clean and dry the nickel-copper composite wire.

4. The preparation method according to claim 1, wherein: The copper-removing solution is made of the following components: nitric acid 30 - 50 g / L, sulfuric acid 100 - 150 g / L, methylbenzotriazole 10 - 15 g / L, and the solvent is water. The soaking time in the copper-removing solution is 40 - 50 min; The electrolyte for electrolytic copper removal is made of the following components: ammonium citrate 100 - 150 g / L, sodium nitrate 150 - 200 g / L; sodium nitrite 50 - 70 g / L, and the solvent is water. When performing electrolytic copper removal, the temperature of the electrolyte is 30 - 40 °C, and the electrolytic voltage is 4 - 6 V.

5. The preparation method according to claim 4, characterized in that, The soaking in the copper-removing solution is used to remove 80% - 90% of the copper on the nickel-copper composite wire, and the electrolytic copper removal is used to remove the residual copper on the nickel-copper composite wire.

6. The preparation method according to claim 2, characterized in that, The water-soluble emulsion is made of the following components: by weight percentage, fatty alcohol polyoxyethylene ether 1.5% - 3.5%, ethanol 0.4% - 1.2%, polyvinyl alcohol 0.08% - 0.25%, sodium benzoate 0.02% - 0.05%, and the balance is water.

7. The preparation method according to claim 1, wherein, The degreasing and activating solution is prepared from the following components: by mass percentage, 1% - 3% of amino-functionalized nano-silicate dispersion, 0.5% - 1.5% of perfluoropolyoxyethylene ether, 4.9% - 14.7% of phosphoric acid, 4.9% - 9.8% of sulfuric acid, 0.1% - 0.5% of PEG-modified HEDP, and the balance is water.

8. The preparation method according to claim 7, wherein The preparation of the amino-functionalized nano-silicate dispersion includes the following steps: Add nano-silicate into deionized water and ultrasonically disperse for 30 min to form a nano-silicate suspension. Adjust the pH of the suspension to 4 - 5 with 0.1 mol / L dilute hydrochloric acid or acetic acid and stir evenly. Slowly drop APTES into the suspension while keeping stirring. Place the mixture in a 60 °C water bath and stir and react for 4 - 6 h. After the reaction ends, separate the solid product by a centrifuge, wash it 3 times with ethanol and deionized water respectively to remove unreacted APTES and by-products. Disperse the washed solid in deionized water, adjust the concentration to 10% - 20%, and ultrasonically disperse for 15 min to obtain the amino-functionalized nano-silicate dispersion.

9. The preparation method according to claim 7, wherein The preparation of the perfluoropolyoxyethylene ether includes the following steps: Add perfluorooctanol into absolute ethanol and stir to dissolve. Add 1% of NaOH based on the mass of perfluorooctanol and stir evenly. Under the protection of nitrogen, heat the reaction kettle to 70 - 80 °C, slowly introduce ethylene oxide gas with a molar ratio 5 - 10 times that of perfluorooctanol, and control the pressure at 0.2 - 0.5 MPa. Keep at 70 - 80 °C, stir and react for 6 - 8 h until ethylene oxide is completely consumed. After the reaction ends, cool to room temperature, neutralize to pH 6 - 7 with dilute hydrochloric acid, add deionized water, let it stand for layering, and take the organic phase. Remove ethanol and water with a rotary evaporator to obtain a viscous perfluoropolyoxyethylene ether product.

10. The preparation method according to claim 7, characterized in that, The preparation of the PEG-modified HEDP includes the following steps: Add dried PEG to remove moisture, 80% - concentrated HEDP, and 1% of p-TSA based on the total mass into a three-necked flask, and add toluene as a dehydrating agent. Under a nitrogen atmosphere, heat to 110 - 120 °C and stir and reflux for 6 - 8 h. After the reaction ends, cool to room temperature, add deionized water to dissolve, let it stand for layering, and take the aqueous phase. Remove residual toluene and water with a rotary evaporator to obtain PEG-modified HEDP.